Exploring the effect of social media on revisit intentions - Sheraz Ahmad; Singha Chaveesuk; Wornchanok Chaiyasoonthorn; Sulaiman Khan (Anatolia, 2024)
After the emergence of COVID-19, the tourism industry changed drastically and experienced a considerable decline. Thus, this study explored the impact of social media during COVID-19 on revisit intentions with the mediating effect of brand commitment and brand happiness based on protection motivation theory (PMT). Survey-based quantitative data was gathered from the tourists, and data analysis was done on SPSS and AMOS. The results exhibit that social media during COVID-19 has a significant positive relationship with revisit intentions, brand commitment, and brand happiness. The study also showed that brand commitment and brand happiness have a significant positive relationship with revisit intentions. The study has also demonstrated a significant positive mediating effect of brand commitment and brand happiness between social media during COVID-19 and revisit intentions.
Keywords: Digital Marketing and Social Media; Technology Adoption and User Behaviour; Customer Service Quality and Loyalty